RIP2 activity in inflammatory disease and implications for novel therapeutics. Issue 5 (1st November 2013) - Jun, Janice C.; Cominelli, Fabio; Abbott, Derek W.
Abstract : Review on the role that the NOD2:RIP2 complex plays in inflammatory disease, with an emphasis on its inhibition as a future drug target. Abstract : The role of NOD2 and RIP2 in inflammatory disease has been paradoxical. Whereas loss‐of‐function NOD2 polymorphisms cause CD, a granulomatous disease of the gastrointestinal tract, gain‐of‐function mutations cause EOS—a granulomatous disease primarily affecting the skin, joints, and eyes. Thus, gain‐of‐function mutations and loss‐of‐function polymorphisms cause granulomatous inflammatory disease, only in different anatomic locations. The situation is complicated further by the fact that WT NOD2 and WT RIP2 activity has been implicated in diseases such as asthma, inflammatory arthritis and MS. This article reviews the role that the NOD2:RIP2 complex plays in inflammatory disease, with an emphasis on the inhibition of this signaling pathway as a novel pharmaceutical target in inflammatory disease.